Role of market orientation in affecting entrepreneurial competencies in turbulent environments / Muhammad Hanif ... [et al.] - Hanif, Muhammad; Abdul Rahim, Mohammad Zulkifli; Qureshi, Imran Munawar; Aftab, Muhammad; Mohsin, Muhammad (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
Entrepreneurship plays a crucial part in advancing the economy. There are very few studies that have examined the outcome of the market orientation (MO) proceeding developing entrepreneurial competencies (EC). We collected data from entrepreneurs in different Pakistani cities using a survey design. A sample size of four hundred and twenty-two was obtained, based on simple random sampling. Regression and moderation analyses were conducted using Jeffrey’s Amazing Statistics Program (JASP). Results suggested a very strong effect of MO in developing EC. Environmental turbulence (ET) also had a significant role in moderating the aforementioned relationship. More so, market oriented firms had a very strong focus on developing and enhancing competencies in highly turbulent environments. Entrepreneurial firms may benefit from this study by considering the benefits of adopting a market orientation. Entrepreneurs should have a strong market orientation, particularly in times characterized by high levels of ET. Future studies can look at the role of dimensions of market orientation and environmental turbulence in effecting specific competencies from multiple contextual perspectives.